Emulation-in-the-loop for simulation and testing of real-time critical CPS - Oliveira, Renato (2018)
Complex cyber-physical systems are more and more a set of components working tightly coupled, with little or no human intervention. Assessing the correctness of these systems by testing components individually, one-by-one, is obviously not sufficient, being required to also test and validate the overall system. KhronoSim is a modular and extensible platform for testing cyber-physical systems in closed-loop, which enables the integration of simulation models and platform emulators to build a closed loop test environment. This paper presents the emulator module of KhronoSim, developed to integrate the well-known QEMU emulator in the closed-loop testing platform.